High-pressure hydrothermal synthesis of shape-controlled AuPt nanoflowers with enhanced electro-catalytic properties for methanol oxidation reaction - Yan Liu; Ziyi Li; Zhao Zhang; Haitao Zhang (Results in Chemistry)
AuPt nanoflowers (NFs) were successfully synthesized by one-pot high-pressure hydrothermal method. The sizes and morphologies of AuPt NFs can be flexibly tailored by adjusting the concentration of cetyltrimethylammonium chloride (CTAC), initial pressure, the concentration ratio of precursor and total precursor concentrations. Our results showed that AuPt NFs prepared using 640 mg CTAC has the characteristics of the largest electrochemical active surface areas (ECSAs), highest CO-tolerance and most excellent methanol oxidation reaction (MOR) catalytic performance because of the maximum Pt utilization. Furthermore, the AuPt NFs prepared using 640 mg CTAC also exhibited the larger ECSAs and the better MOR catalytic performance than those of Pt nanoparticles (NPs) alone and commercial Pt black. The mass-normalized current densities for MOR in the presence of AuPt NFs was approximately 3.1 and 5.9 times higher than those of Pt NPs and commercial Pt black, respectively. Therefore, it proves that the method of the size and morphology control synthesized of AuPt NFs can suitable optimize the design of Pt-based catalysts for direct methanol fuel cells (DMFCs).